Association Between the Surrogate Markers of Insulin Resistance and Chronic Kidney Disease in Chinese Hypertensive Patients - Shi, Yumeng; Hu, Lihua; Li, Minghui; Zhou, Wei; Wang, Tao; Zhu, Lingjuan; Bao, Huihui; Cheng, Xiaoshu; Li, Ping (Frontiers in Medicine, 2022)
Background: We aim to evaluate the four surrogate markers of insulin resistance (IR), including triglyceride-glucose index (TyG), lipid accumulation product index (LAP), visceral adiposity index (VAI), triglycerides to high-density lipoprotein cholesterol ratio (TG/HDL), on the prevalence of chronic kidney disease (CKD) and to examine any possible effect modifiers in Chinese hypertensive patients. Methods: A total of 13055 hypertensive participants were included in this cross-sectional study. In addition, the average age of the study population was 63.81±9.46 years, and 47.66% of them are men. The primary outcome was CKD, defined as eGFR < 60mL/min/1.73 m2. Multivariate logistic regression analysis and the generalized additive model and a fitted smoothing curve (penalized spline method) were used to examine the association between the surrogate markers of IR and CKD. Results: Four surrogate markers of IR were independently and positively associated with CKD in a dose-response fashion. The association between four surrogate markers of IR and the prevalence of CKD was examined as a continuous variable per 1 unit increment and also as a categorical variable using tertiles with the tertiles (T1) as the reference group. In the fully adjusted model, multivariate logistic analyses showed that the per 1 unit increments of the TyG, LAP, VAI, and TG/HDL ratios were all significantly associated with 42, 31, 67, and 78% higher risk for CKD, respectively. Consistently, the adjusted ORs (95% CI) for CKD were 1.48 (1.21, 1.81), 1.34 (1.06, 1.69), 1.26 (1.03, 1.53), 1.35 (1.12, 1.63) when comparing the highest tertile to the lowest tertile of the TyG, LAP, VAI, and TG/HDL ratios, respectively. The stratification analysis showed that a significant positive correlation between TyG, VAI, and TG/HDL and CKD in patients over 65 years old. Conclusion: Four surrogate markers of IR were independently and positively correlated with CKD, and LAP was better than the other surrogate markers of IR for predicting CKD. Only among participants aged over 65 years were higher levels of TyG, VAI, and TG/HDL found to be closely related to the increased prevalence of CKD.